Radość Sydoniusza Apolinarego z tego, że filozofia służy teologii - Grzywaczewski, Józef (Vox Patrum, 2012)
The article shows Sidonius Apollinaris’ admiration for all intellectual activities. For example he congratulated Faustus of Riez after reading his book „On the Holy Spirit”. In all the Sydonius’ writings one can see that he has always had a lot of respect for poets and writers as Lampridius or to scholars as Phoebus. In the context of the fall of the Roman Empire Sidonius really appreciated those who reach for the teachings of ancient philosophy, rhetoric, astronomy and music in the proclamation of the Gospel. So Claudianus Mamertus, author of the book „De statu animae” did. According to Sidonius he was a great master of the three cultures: Roman, Greek and Christian. In the works of Sidonius we can see a gradual transition from the vision of the Empire as a political power to the vision of the Church as a spiritual power. In this context, he gladly stated that the Plato’s Academy was working for the Church of Christ. For this reason, he appreciated each quotation from pagan’s works in Christian works. Polish reader can see common elements in Sidonius and Sienkiewicz: both writers were living in a difficult political situation, the home of the two was ruled by foreign rulers: both writers set themselves the same goal – to write to encourage hearts with glorification of excellent people. Both writers wanted to help people get out of the crisis and to lay the foundations for a better future.